Employee Motivation in the Uniformed Services – A Bibliometric Analysis - Joanna Szydło; Zuzanna Sara Moczydłowska (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2025)
Aim: This article aimed to systematise knowledge of motivation in the uniformed services and identify directions for future research.